PARAMETER OPTIMIZATION AND CRASHWORTHINESS STUDY OF A NOVEL POROUS SANDWICH STRUCTURE BASED ON VORONOI ALGORITHM - WANG Shuai; SUN Nan; CHEN Zhuo; ZHOU KaiFa (Jixie qiangdu)
The enhancement of truck mounted attenuators(TMAs)crashworthiness is an important way to protect vehicle safety.A new porous structure was generated by Voronoi algorithm.Firstly,the influence of the parameter,the seed number n,porosity of the structureρand irregularityαof porous structure on geometric topology was studied.The mathematical model between the specific energy absorption and the three parameters was established.Then,by the finite element method,the energy absorption of the new structure was analyzed,and the reliability of the mathematical model was confirmed.The optimal structural parameters were determined by orthogonal experiment.Finally,the new porous structure was filled into the TMAs as a sandwich,and the crashworthiness of the vehicle under three working conditions(forward collision,side collision and oblique collision)was discussed.It is found that the new porous structure can effectively reduce the peak impact force,and its energy absorption performance is far better than that of traditional TMAs and cylindrical sandwich TMAs,which can effectively protect the safety of crashed vehicles and drivers.